The human intranet - Where swarms and humans meet - Rabaey, Jan M. (2015 Design, Automation & Test in Europe Conference & Exhibition (DATE), 2015)
A Human Intranet is envisioned as an open scalable platform that seamlessly integrates an ever-increasing number of sensor, actuation, computation, storage, communication and energy nodes located on, in, or around the human body acting in symbiosis with the functions provided by the body itself. This may fundamentally alter the ways humans operate, and interact with the physical world around them. It all starts with concepts that find their roots in the Internet of Things (IoT) and swarm technologies.